“Identity theft” in BRCA1/2: impact of positive genetic test results and risk-reducing interventions - Adler, Jonathan M.; Hesse-Biber, Sharlene; Seven, Memnun; Dwyer, Andrew A. (Frontiers in Genetics, 2024)
Individuals harboring breast cancer gene 1/2 (BRCA1/2) pathogenic variants are at increased lifetime risk for developing cancer. Learning one's BRCA1/2 carrier status is a watershed moment that can result in psychological distress, anxiety, and depression, as well as feelings of vulnerability and stigma. However, emotional and coping responses to learning one's BRCA1/2 carrier status and after risk-reducing interventions (i.e., preventative bilateral mastectomy) are variable, and existing literature reveals mixed and sometimes contradictory results. Drawing on the concept of narrative identity from the field of psychology, we sought to examine if 'identity theft' (the sudden overtaking of one's narrative agency by an external force) may help explain the heterogeneity of emotional and coping responses following the revelation of BRCA carrier status and the subsequent medical intervention one may receive. This Perspective explores BRCA related identity theft using two case studies. Narrative analysis of qualitative interviews uncover the ways that patients experience the disintegration (theft) of their identity as well as their efforts to build and reintegrate a new BRCA carrier identity. This initial qualitative exploration provides preliminary support for the relevance of narrative identity and identity theft to hereditary cancer. We posit that applying the lens of identity theft may hold promise as a unifying concept, integrating across the variable emotional and coping responses among BRCA carriers. Employing a lens of identity theft may help inform the development of tailored narrative interventions as part of precision healthcare to support active coping and psychosocial wellbeing.